Association between serum secretory phospholipase A2 and risk of ischaemic stroke. (30th July 2021) - Smith, Jed W.; Barlas, Raphae S.; Mamas, Mamas A.; Boekholdt, S. Matthijs; Mallat, Ziad; Luben, Robert N.; Wareham, Nicholas J.; Khaw, Kay‐Tee; Myint, Phyo K.
Abstract: Background and purpose: Previous literature has demonstrated an association between high serum levels of type II secretory phospholipase A2 (sPLA2) concentration and an increased risk of coronary artery disease. However, such association has not been established in terms of ischaemic stroke risk. The aim was to evaluate the association between both sPLA2 concentration and activity as continuous variables with risk of future ischaemic stroke. Methods: A nested case–control study was conducted using data from the European Prospective Investigation into Cancer—Norfolk study. Cases ( n  = 145) in the current study were participants who developed ischaemic stroke during follow‐up, with controls ( n  = 290) matched in a 2:1 ratio based on age and sex. Statistical analyses were performed using SPSS (version 25.0) software. Logistic regression was used to determine odds ratios (OR) and corresponding 95% confidence intervals (95% CIs) for ischaemic stroke. Results: After adjusting for a wide array of cardiovascular confounders, sPLA2 activity was found to be associated with an increased risk of ischaemic stroke using both multiple imputations with chained equations and complete case analysis: OR 1.20 (95% CI 1.01–1.43) and OR 1.23 (95% CI 1.01−1.49), respectively. However, sPLA2 concentration was not found to be associated with increased risk of ischaemic stroke. Conclusions: The activity of sPLA2, but not sPLA2 concentration, is associated with an increased risk of future ischaemic stroke. This finding may be significant in risk group stratification, allowing targeted prophylactic treatment, or the development of novel therapeutic agents. Abstract : Despite an association between high serum levels of type II secretory phospholipase A2 (sPLA2) concentration and an increased risk of coronary artery disease being previously demonstrated, this association has not been assessed in terms of risk of ischaemic stroke. A nested case–control study was conducted using data from the European Prospective Investigation into Cancer—Norfolk study to evaluate the association between both sPLA2 concentration and activity as continuous variables with risk of future ischaemic stroke. It was found that sPLA2 activity, but not concentration, is associated with an increased risk of ischaemic stroke, independent of traditional cardiovascular risk factors.